2001
DOI: 10.1590/s0074-02762001000300022
|View full text |Cite
|
Sign up to set email alerts
|

Courtship song genes and speciation in sand flies

Abstract: Lutzomyia longipalpis (Lutz & Neiva, 1912)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…The values of the Tajima parameter (D) were -0.73333 (P > 0.10) for the field population and -0.30187 (P > 0.10) for the laboratory colony, so that selection can be discounted as being responsible for the diversity encountered (Table 1) and the F ST value calculated between both populations was 0.37179 (P = 0.05), suggesting that there is a considerable degree of genetic differentiation between them. Similar values have been discovered when comparing divergent geographic populations in insect vectors of pathogens (Oliveira et al 2001). The analyses of maximum probability of the cytochrome b gene under the model HKY (Hasegawa et al 1985) produced the tree shown in Fig.…”
Section: Resultssupporting
confidence: 73%
“…The values of the Tajima parameter (D) were -0.73333 (P > 0.10) for the field population and -0.30187 (P > 0.10) for the laboratory colony, so that selection can be discounted as being responsible for the diversity encountered (Table 1) and the F ST value calculated between both populations was 0.37179 (P = 0.05), suggesting that there is a considerable degree of genetic differentiation between them. Similar values have been discovered when comparing divergent geographic populations in insect vectors of pathogens (Oliveira et al 2001). The analyses of maximum probability of the cytochrome b gene under the model HKY (Hasegawa et al 1985) produced the tree shown in Fig.…”
Section: Resultssupporting
confidence: 73%
“…Most commonly, these markers are sequenced alone or coupled to one or two others. The most frequent are genes coding for lovesongs: period (Bauzer et al, 2002a,b;Mazzoni et al, 2002Mazzoni et al, , 2006Mazzoni et al, , 2008Araki et al, 2009;Salomon et al, 2010;Vigoder et al, 2010) and cacophony (Oliveira et al, 2001;Lins et al, 2002;Bottecchia et al, 2004;Mazzoni et al, 2008;Depaquit et al, 2014) Valderrama et al, 2014). Other markers have only been used one time each: copulatory courtship songs: , Reverse transcriptase (Booth et al, 1991), Non-LTR retrotransposons (Booth et al, 1994), para genes: , Ca1D , Rp49 , maxadilan (Yin et al, 2000) and SP15-Saliva protein (Elnaiem et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This fragment includes an intron missing in Drosophila (Peixoto et al. , 1997) that is polymorphic in L. longipalpis (Oliveira et al. , 2001).…”
Section: Introductionmentioning
confidence: 99%